The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/are.13074
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diet supplemented with Lactobacillus rhamnosus on tissue parameters of rainbow trout, Oncorhynchus mykiss (Walbaum)

Abstract: This study was carried out to establish the effects of a 6 week treatment with the diet supplemented with L. rhamnosus in concentrations of 107 CFU g−1 (G1 group) and 108 CFU g−1 (G2 group) on the condition expressed by condition factors (Fulton's, Clark's and B), intestinal microbiology, haematological, histological and selected antioxidative parameters of rainbow trout. A significantly higher condition factors were found in G1 group indicating that higher concentration of probiotic (108 CFU g−1) did not resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The supplementation of probiotics and/or prebiotics into the diet of fish is believed to result in beneficial alterations of the gut microbiota and subsequent changes in metabolism and energy expenditure that are beneficial for the host (119, 123, 124). The administration of these supplements also enhance immune function of the host and increase its resistance to pathogens, enhancing general health and indirectly favoring feeding and growth (125). These effects highlight the potential for probiotics/prebiotics to enhance fish health by manipulating the fish gut microbiota.…”
Section: Gut Microbiota Manipulation and Applicationsmentioning
confidence: 99%
“…The supplementation of probiotics and/or prebiotics into the diet of fish is believed to result in beneficial alterations of the gut microbiota and subsequent changes in metabolism and energy expenditure that are beneficial for the host (119, 123, 124). The administration of these supplements also enhance immune function of the host and increase its resistance to pathogens, enhancing general health and indirectly favoring feeding and growth (125). These effects highlight the potential for probiotics/prebiotics to enhance fish health by manipulating the fish gut microbiota.…”
Section: Gut Microbiota Manipulation and Applicationsmentioning
confidence: 99%
“…rhamnosus on red sea bream (Dawood et al, 2017 ), showed significant increase of plasma and mucus parameters (total protein, mucus myeloperoxidase activity, and mucus secretion), and concluded the results to be a sign for beneficial effects on host physiological responses. In a study with rainbow trout, Popovic et al ( 2017 ) investigated the effect of dietary Lb. rhamnosus (10 7 and 10 8 CFU g −1 ) on intestinal microbiota and histology, biochemical parameters, and antioxidant defense in a 6-weeks feeding trial.…”
Section: Lab As Probioticmentioning
confidence: 99%
“…The authors concluded that Lb. rhamnosus was a promising feed additive, capable of improving rainbow trout health (Popovic et al, 2017 ).…”
Section: Lab As Probioticmentioning
confidence: 99%
“…When incorporated into the diet, the probiotic bacteria proliferate within the existing microbiome, compete with pathogens for nutrients and space, and help to maintain a healthy microbial balance 93,98 . Interest in this area of research is growing and many experiments have investigated the beneficial effects of probiotics and prebiotics 99–102 . For example, Bacillus and Lactobacillus are two types of probiotic bacteria commonly used in aquaculture that have demonstrated the capacity to improve fish health.…”
Section: Alternative Strategies For Disease Prevention and Mitigationmentioning
confidence: 99%